La frontière, interface des trafics dans le Triangle d’or - Pierre-Arnaud Chouvy (L'Espace Politique)
From opiates to amphetamine-type stimulants, drug production and drug trafficking have evolved over a few decades in the so-called Golden Triangle, in the heart of the Indochinese peninsula’s fan-shaped highlands. The region, a three-border area made of peripheral and marginal highlands and populated by a wide array of ethnic groups, is as complex as its many illegal trades. Routes, borders and other spatial discontinuities are the backbones of the large drug producing and trafficking activities that define the Golden Triangle, but also, to some extent, of the armed conflicts and the counter-narcotics that make the illegal drug industry a feasible and profitable business.